Lighting Recommendation on Flat Lay Photography Technique for Stopmotion Purpose - Diana Aqidatun Nisa; Alfian Candra Ayuswantana; Muhammad Mashuda; Shinta Rahma Puspita; Octaviasari (Future Science, 2022)
The existence of lighting greatly affects the results of photographic shots. By creating lighting, it can produce different nuances and feelings. Lighting is influenced by light quality, light intensity, and light source. When shooting indoors, the light source can ideally be created using various types of studio lights. This article describes lighting recommendations on flat-lay photography techniques suitable for stop motion. The method used in this research is descriptive qualitative through a visual photography experimental study approach. Data collection resulted from direct experiments by applying the Flat Lay photography technique. In addition, literature studies support the experiment. The experiment was carried out in an indoor room. The results of photography trials regarding lighting on clay figure objects must have no shadows or minimal shadows. The virtual line between the light and shadow boundaries should be blurred. In addition, the figure should not be too bright or too dim so that the figure's details clearly visible.